2008
DOI: 10.1177/1545968308329922
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Based Electrical Stimulation Training in a Stroke Patient With Minimal Movement in the Paretic Upper Extremity

Abstract: Although conventional paretic upper extremity training strategies are ineffective in patients at this level, electrical stimulation training incorporating a neuroprosthesis appears promising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Furthermore, proprioceptive sensory feedback might play an important role in this kind of therapy. The results of the single-case study from Page et al (2009) supports these promising results. Moreover, another recent single-case study supports the benefit of a combination of FES and BCI (Daly et al, 2009).…”
Section: Motor Substitutionmentioning
confidence: 60%
“…Furthermore, proprioceptive sensory feedback might play an important role in this kind of therapy. The results of the single-case study from Page et al (2009) supports these promising results. Moreover, another recent single-case study supports the benefit of a combination of FES and BCI (Daly et al, 2009).…”
Section: Motor Substitutionmentioning
confidence: 60%
“…Thus, we examined whether the addition of FES improved the quality and recovery of hand function during training. The Bioness H200 device was selected for this study, because it is designed for easy donning and doffing, making it suitable for participants to take home and use reliably on a daily basis 25-26. The rationale for combining FES, OnabotulinumtoxinA, and task practice was that boosting muscle contractile force with FES and relaxing spasticity with OnabotulinumtoxinA would improve motor performance during task practice training.…”
Section: Discussionmentioning
confidence: 99%
“…38 Based on these findings the authors suggest that the H200 could be used as a 'gateway' or 'bridge' to participation in therapy regimes that demand greater volitional activity than is available to the stroke survivor with severe paresis, in particular constraint induced movement therapy. 33,38,39 This indicates that neuroprostheses can be used to not only replace, but also retrain UL function.…”
Section: Neuroprosthesesmentioning
confidence: 96%
“…17,45 When considering stroke survivors with little or no volitional activity, a controlled study reported improvements in both impairment (spasticity, active ROM) and hand activity (BBT, JTHFT). 29 Similarly, in a number of single case studies of stroke survivors with no active extension of the wrist or fingers, reduced impairment (FMA), increased activity (ARAT, Arm Motor Ability Test) 31,39 and participation (Stroke Impact Scale and Motor Activity Log) 31 was demonstrated. More recently, it has been found that repetitive taskspecific training for 20 hours over 8 weeks can lead to an increase in cortical activation, which the authors believe was associated with an increased use of the arm.…”
Section: Neuroprosthesesmentioning
confidence: 96%